Multilevel Spinal Canal Stenosis with Ossification of the Ligamentum Flavum in an Achondroplastic Patient : A Case Report - Widyatama, Arya; Moeljono, Adam (Rumah Sakit Akademik Universitas Gadjah Mada, 2022)
Achondroplasia is the most common form of dwarfism in humans. There are abnormalities of intracartilaginous ossification caused by mutation of FGFR 3 gene resulting in a narrow spinal canal accompanied by neurological impairements in some patients. The neurological impairements could be caused by ossification of ligamentum flavum, disc degeneration, kyphosis of lumbar spine, bony spurs, thickened laminae and facet joints. We reported a case of 23-year-old Indonesian male with achondroplasia, spinal canal stenosis accompanied by ossification of ligamentum flavum presented with progressive myelopathy and neurogenic claudication. Spinal canal stenosis with OLF was observed at L2-L5 level of lumbar spine. Laminectomy with decompression and removal of the OLF was performed at L2-L5. There was an improvement on patient's neurological symptoms and function after the surgery. In this report, we describe a rare case of achondroplasia with OLF presenting with neurological symptoms from multiple level of spinal canal stenosis. We perfromed decompressive wide laminectomy and resection of adherent OLF followed by fusion with instrumentation resulted in the improvement of patient's neurological symptoms and function.